IMPROVEMENT OF BIOETHANOL PRODUCTION BY USING Saccharomyces cerevisiae [Meyen ex E.C. Hansen] IMMOBILIZED ON PRETREATED SUGARCANE BAGASSE - Sita Heris Anita; Wibowo Mangunwardoyo; Yopi Yopi (Dept. of Chemical Engineering, Diponegoro University, 2018)
Pretreated of sugarcane bagasse was used as a carrier for immobilization of Saccharomyces cerevisiae. Pretreatments were carried out by steaming, pressurized steam, and combination both of procedure. The objectives of this research was to investigate the effect of pretreatment on sugarcane bagasse to cells adsorption and bioethanol production. Immobilization process was conducted in a ratio of 2.5 g carrier/50 mL cell suspension. Whole cell biocatalyst as much as 1% (w/v) was used as inoculum for bioethanol fermentation. The best pretreated sugarcane bagasse for carrier of immobilized cells was obtained using steam treatment for 30 minutes. Those treatment improved the physical properties of carrier and increased the cell retention up to 10.05 mg/g. The use of whole cell biocatalyst after steaming pretreatment also enhanced ethanol yield 1.5 times higher than control. Keywords: bioethanol; immobilization; pretreatment; steam treatment; sugarcane bagasse